2006
DOI: 10.1158/1535-7163.mct-06-0184
|View full text |Cite
|
Sign up to set email alerts
|

1,1-Bis(3′-indolyl)-1-(p-substituted phenyl)methanes inhibit ovarian cancer cell growth through peroxisome proliferator–activated receptor–dependent and independent pathways

Abstract: 1,1-Bis(3′-indolyl)-1-(p-t-butylphenyl)methane (DIM-C-pPhtBu) is a peroxisome proliferator–activated receptor γ (PPARγ) agonist, and treatment of SKOV3 ovarian cancer cells with this compound (5 μmol/L) inhibits cell proliferation, whereas up to 15 μmol/L rosiglitazone had no effect on cell growth. DIM-C-pPhtBu also inhibits G0-G1 to S phase cell cycle progression and this is linked, in part, to PPARγ-dependent induction of the cyclin-dependent kinase inhibitor p21. DIM-C-pPhtBu induces PPARγ-independent down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 56 publications
5
53
0
Order By: Relevance
“…Previous studies have found greater pro-apoptotic responses to other synthetic DIM derivatives. For example, a set of 1,1-bis(3′-indolyl)-1-(p-substituted-phenyl)methanes (C-DIMs), carrying paratrifluoromethyl-, t-butyl-, phenyl-, cyano-, or methoxy-groups have previously been shown to activate anti-proliferative and pro-apoptotic pathways, and this was due in part to their activity as ligands for peroxisome proliferator-activated receptor γ (PPARγ) and NR4A1 (TR3/Nur77); these same compounds also induced ER stress in pancreatic, ovarian and colon cancer cells [19,25,[27][28][29]. Other chemically modified dietary compounds such as brominated vanillin (a flavour compound) and chlorinated flavonoids have been shown to kill Jurkat leukemia cells and hepatocarcinoma cells, respectively, at concentrations lower than the parent molecule by activating down-stream effectors of apoptosis such as caspase-3, resulting in nuclear DNA fragmentation and chromatin condensation [42,43].…”
Section: Ring-dims Induce Death Of Androgen-dependent and -Independenmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found greater pro-apoptotic responses to other synthetic DIM derivatives. For example, a set of 1,1-bis(3′-indolyl)-1-(p-substituted-phenyl)methanes (C-DIMs), carrying paratrifluoromethyl-, t-butyl-, phenyl-, cyano-, or methoxy-groups have previously been shown to activate anti-proliferative and pro-apoptotic pathways, and this was due in part to their activity as ligands for peroxisome proliferator-activated receptor γ (PPARγ) and NR4A1 (TR3/Nur77); these same compounds also induced ER stress in pancreatic, ovarian and colon cancer cells [19,25,[27][28][29]. Other chemically modified dietary compounds such as brominated vanillin (a flavour compound) and chlorinated flavonoids have been shown to kill Jurkat leukemia cells and hepatocarcinoma cells, respectively, at concentrations lower than the parent molecule by activating down-stream effectors of apoptosis such as caspase-3, resulting in nuclear DNA fragmentation and chromatin condensation [42,43].…”
Section: Ring-dims Induce Death Of Androgen-dependent and -Independenmentioning
confidence: 99%
“…The diverse molecular targets through which DIM is assumed to exert its anti-proliferative and pro-apoptotic effects have not been identified and DIM-induced necrosis has not been examined. Moreover, the search for compounds exhibiting higher potency and specificity towards prostate tumours is ongoing, and we have studied a number of methyl-substituted derivatives of DIM in other cancerous tissues [19,[25][26][27][28][29][30]. More recently, we have begun to test halogenated forms of the compound in AD prostate cancer cell models [31].…”
Section: Introductionmentioning
confidence: 99%
“…20). These PPARg agonists inhibited growth and induced apoptosis in breast, pancreatic, colon, bladder, leukemia, and other cancer cell lines through both receptor-dependent and receptor-independent pathways (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, the effect of rosiglitazone on cancer cells can be either PPARg-dependent or independent, despite it being a potent and highly selective agonist for PPARg. 24,25 Thus, the effect of rosiglitazone on cancer cells may be highly tumor and cell type-specific, and it may not be practical to use it as a monotherapy.…”
mentioning
confidence: 99%